1981
DOI: 10.1266/jjg.56.357
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome aberrations induced by mitomycin c treatment in early spermatids of male mice.

Abstract: Evidence that MC-induced dominant lethal mutations in early spermatids are attributable to chromosome aberrations was obtained through cytogenetic analysis of first-cleavage metaphases.Male mice were intravenously injected with 5 mg/kg of mitomycin C (MC). These males were serially mated with females during 6 weeks after treatment.Chromosome slides were prepared from eggs collected from the ampulla. The maximum frequencies of chromosome aberrations in male pronuclei in the eggs were obtained in early spermatid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1983
1983
1995
1995

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Katoh 1979;Katoh and Tanaka 1980) in the germ cell stages, UDS was observed from spermatocytes to early and mid spermatids, except spermatozoa and late spermatids. The frequencies of MMS-induced chromosome aberrations decreased in early and mid spermatids showing UDS (Brewen et al 1975;Katoh and Tanaka 1980;Tanaka et al 1981). On the other hand, in the case of X-ray, the formation of chromosome aberrations in early and mid spermatids showing UDS indicated an increase than that in spermatozoa and late spermatids showing no UDS.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Katoh 1979;Katoh and Tanaka 1980) in the germ cell stages, UDS was observed from spermatocytes to early and mid spermatids, except spermatozoa and late spermatids. The frequencies of MMS-induced chromosome aberrations decreased in early and mid spermatids showing UDS (Brewen et al 1975;Katoh and Tanaka 1980;Tanaka et al 1981). On the other hand, in the case of X-ray, the formation of chromosome aberrations in early and mid spermatids showing UDS indicated an increase than that in spermatozoa and late spermatids showing no UDS.…”
Section: Discussionmentioning
confidence: 87%
“…Such unrepairable breaks and residual lesions might be related to the formation of chromosome-type aberration. With regard to the increase of chromosome aberrations in early and mid spermatids by X-ray, in addition, there is a possibility that the premutational lesions caused in this stages can be modified to new non-repairable damage during the long maturation process of sperm, as shown in spermatozoa and late spermatids in the case of MMS (Tanaka et al 1981).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies (Tanaka 1981) have also shown that the sensitivity to chemical mutagens in terms of the induction of chromosome aberrations in postcopulation germ cells and zygotes of female mice was high at 7h before ovulation, at least in the cases of MMS and MC treatment.…”
Section: Introductionmentioning
confidence: 81%
“…with Hanks' solution alone. At the time of treatment, the oocytes were at MI-MIT stage just before ovulation, while sperms were in the oviduct and uterus, as shown in earlier studies (Tanaka 1981). All F1 male progeny from the MMS-100 group and the MC-4 group were tested for fertility, while one hundred F1 males each in the MC-3 group and control group were randomly selected from the F1 progeny.…”
Section: Methodsmentioning
confidence: 99%